Nesting Associations without Interdependence: A Preliminary Review on Plesiobiosis in Ants - Orsolya Kanizsai; Gábor Lőrinczi; László Gallé (Psyche: A Journal of Entomology)
Plesiobiosis, the most basic form of interspecific associations in ants, denotes occasional or regular nesting of heterospecific colonies of certain species pairs in close proximity to each other without biological interdependence. Plesiobionts differ from each other both in morphology and in behaviour (e.g., in their foraging strategies), and at least one of the plesiobiotic pair is a submissive species. Recent studies on plesiobiosis have revealed that Formica fusca and Lasius flavus are two of the most frequent plesiobionts. To date, at least 48 different plesiobiotic species pairs have been recorded from various habitat types of the Holarctic region. Two main habitat properties may play a role in the forming of plesiobiosis: the scarcity of suitable nesting sites as a forcing factor and the sufficient amount of food sources available, influencing the abundance of colonies. Thus, high colony density may contribute to the formation of such associations, resulting in (1) frequent nesting in each other's neighbourhood and (2) stronger intraspecific competition, which forces colonies into the vicinity of heterospecific nests. Plesiobiotic associations formed this way may promote persistent coexistence, leading to the formation of other types of interspecific associations (e.g., clepto- or lestobiosis).